2018
DOI: 10.1055/s-0038-1636932
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Complications after Right Hepatectomy for Live Liver Donation: Largest Single-Center Western World Experience

Abstract: The authors assessed the incidence, management, and risk factors for postoperative complications after right lobe (RL) live donor hepatectomy in a high-volume center in North America. All donors undergoing an RL live donor hepatectomy between 2000 and 2017 at our institution were included. The primary outcome was the development of complications (both medical and surgical). Predictors of postoperative complications were determined by logistic regression. A total of 587 patients underwent RL live donor hepatect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 40 publications
(58 reference statements)
2
42
0
Order By: Relevance
“…The complication rate after LLDH varies widely in the literature, between 9 and 40% (8,9,12,(14)(15)(16)(17)(18)(19)21,22). Among our donors, 19.5% experienced complications, comparable with the literature.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The complication rate after LLDH varies widely in the literature, between 9 and 40% (8,9,12,(14)(15)(16)(17)(18)(19)21,22). Among our donors, 19.5% experienced complications, comparable with the literature.…”
Section: Discussionsupporting
confidence: 84%
“…A data review of more than 300 articles, including nearly 6000 LLDH, has reported an overall mortality rate of 0.2% (10,13). Many single-center experiences with the same complication rate have been reported from Turkey and other countries (8,9,(14)(15)(16)(17)(18)(19).We reported briefly our complications in the first 419 LLDH cases in a previous manuscript (20). Including these reported cases, in our first 939 living liver donors, no death occurred related to surgery or complications in our program.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…80 After live donation, the rate of overall postoperative complications is reported to be around 25-30%, with major complications occurring in 9-10% of patients. 80,81 Donor mortality has also been reported and estimated between 0.1-0.3%. 82,83 LT for HCC: future prospects The future direction of LT for HCC will focus on the identification of patients at higher risk of recurrence to prevent futile transplantation.…”
Section: Use Of Marginal Graftsmentioning
confidence: 99%